2020
DOI: 10.1371/journal.pone.0230290
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-based total intravenous anesthesia is associated with better survival than desflurane anesthesia in robot-assisted radical prostatectomy

Abstract: Background Previous researches have shown that anesthetic techniques may influence the patients' outcomes after cancer surgery. Here, we studied the relationship between the type of anesthetic techniques and patients' outcomes following elective robot-assisted radical prostatectomy. Methods This was a retrospective cohort study of patients who received elective, robot-assisted radical prostatectomy between January 2008 and December 2018. Patients were grouped according to the anesthesia they received, namely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 48 publications
1
26
2
Order By: Relevance
“…10% in 100% oxygen at a flow of 0.3 L/min in a closed breathing system in the desflurane group. Repetitive bolus injections of fentanyl and cisatracurium were used as needed during surgery [16][17][18]. Desflurane or maintenance of the Ce with TCI using propofol was adjusted downward and upward by 0.5-2% or 0.2-0.5 μg/mL, respectively, when needed based on the hemodynamics.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…10% in 100% oxygen at a flow of 0.3 L/min in a closed breathing system in the desflurane group. Repetitive bolus injections of fentanyl and cisatracurium were used as needed during surgery [16][17][18]. Desflurane or maintenance of the Ce with TCI using propofol was adjusted downward and upward by 0.5-2% or 0.2-0.5 μg/mL, respectively, when needed based on the hemodynamics.…”
Section: Plos Onementioning
confidence: 99%
“…The level of ETCO2 was kept at 35-45 mmHg by adjusting the ventilation rate with a maximum airway pressure < 30 cm H 2 O. After surgery, cases were transferred to the postanesthesia or intensive care unit and evaluated by the anesthesiologist in charge [16][17][18].…”
Section: Plos Onementioning
confidence: 99%
“…9 Additionally, another retrospective cohort study found that propofol anaesthesia was related to better OS and a lower postoperative biochemical recurrence rate than those with desflurane anaesthesia in patients undergoing robot-assisted radical prostatectomy. 85 However, these previous studies have the limitations of most retrospective investigations. Hence, a prospective trial was warranted to evaluate the effect of propofol on bladder cancer outcomes.…”
Section: Effec T Of Prop Ofol On the Prog Nos Is Of Patients With Cmentioning
confidence: 99%
“…Notably, a meta‐analysis study including 7866 patients with different types of cancer discovered that the use of propofol improved the OS and RFS of cancer in comparison with the use of inhalational anaesthesia 9 . Additionally, another retrospective cohort study found that propofol anaesthesia was related to better OS and a lower postoperative biochemical recurrence rate than those with desflurane anaesthesia in patients undergoing robot‐assisted radical prostatectomy 85 . However, these previous studies have the limitations of most retrospective investigations.…”
Section: Effect Of Propofol On the Prognosis Of Patients With Cancermentioning
confidence: 99%
“…Currently, surgical resection is only possible curative treatment for pancreatic cancer. However, surgical intervention might impair cell-mediated immunity and activated circulating tumor cells implantation which leave patients susceptible to develop of postoperative recurrence or metastasis 3 , 4 . Multiple retrospective studies have shown that regional anesthesia improved patient outcome after surgery in bladder, breast and lung cancers 5 - 7 .…”
Section: Introductionmentioning
confidence: 99%